Use of immunohistochemical staining panel for characterisation of ovarian neoplasms. Issue 1 (January 1988) - Ashorn, P; Helle, M; Helin, H; Ashorn, R; Krohn, K
Abstract : Eighty five ovarian epithelial and non-epithelial tumours were studied by peroxidase histochemical staining for their reactivity with six monoclonal human milk fat globule (HMFG) antibodies, peanut agglutinin (PNA) lectin, and a monoclonal cytokeratin antibody. HMFG IIIC12 and cytokeratin antibodies distinguished epithelial from non-epithelial tumours. The staining patterns of mucinous and serous tumours were essentially different from each other; poorly differentiated anaplastic carcinomas showed similar antigenic content to that of the serous cystadenocarcinomas. Furthermore, staining with PNA lectin and HMFG antibodies was useful in distinguishing clear cell carcinomas from other malignant epithelial tumours of the ovary.